Accessing microenvironment compartments in formalin-fixed paraffin-embedded tissues by protein expression analysis. (November 2013) - Donnarumma, Fabrizio; Végvári, Ákos; Rezeli, Melinda; Welinder, Charlotte; Jansson, Bo; Marko-Varga, György
Background: Formalin-fixed paraffin-embedded (FFPE) samples are an outstanding source of new information regarding disease evolvements. Current research on new biomarkers and diseases features has recently invested resources in FFPE-related projects.Results: In order to initiate clinical protein-expression studies using minute amount of biological material, a workflow based on the combination of filter-assisted sample preparation with MS analysis and label-free quantification was developed. Xenograft lung tumor tissue was investigated as a model system. The workflow was optimized and characterized in terms of its reproducibility from a quantitative and qualitative point of view. We proposed a modification of the original filter-assisted sample preparation protocol to improve reproducibility and highlight its potential for the investigation of hydrophobic proteins.Conclusions: Altogether the presented workflow allows analysis of FFPE samples with improvements in the analytical time and performance, and we show its application for lung cancer xenograft tissue samples.